Mobility induces global synchronization of oscillators in periodic extended systems - Peruani San Román, Fernando Miguel (2010)
We study the synchronization of locally coupled noisy phase oscillators that move diffusively in a one-dimensional ring. Together with the disordered and the globally synchronized states, the system also exhibits wavelike states displaying local order. We use a statistical description valid for a large number of oscillators to show that for any finite system there is a critical mobility above which all wave-like solutions become unstable. Through Langevin simulations, we show that the transition to global synchronization is mediated by a shift in the relative size of attractor basins associated with wavelike states. Mobility disrupts these states and paves the way for the system to attain global synchronization. © IOP Publishing Ltd and Deutsche Physikalische Gesellschaft.